Investigation of the effect of kinetic brain exercises on agility and attention in tennis beginner - Atay, Emrah (Progress in Nutrition, 2020)
Study Objectives: The aim of this study was to investigate the effects of kinetic brain exercises on attention and agility in beginners of tennis. Methods: Ten people with mean age of 23.70±0.21 years, a mean height of 1.69±0.03 m, and a mean body weight of 69.50±13.95 kg participated in the study voluntarily. In addition to basic tennis skill training, the participants were given 30 minutes of kinetic brain exercises 3 days a week for 10 weeks. D2 attention test and agility test were applied to determine the change in the performance of the participants. The data were analyzed in SPSS 22 statistical program and the Paired-T test was applied in statistical analysis, the significance value was determined as p0.05). Significant improvement was observed in the concentration and agility scores of the participants (p